2011
DOI: 10.1002/jssc.201000541
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of 13 phytohormones in oilseed rape tissues by liquid chromatography‐electrospray tandem mass spectrometry and the evaluation of the matrix effect

Abstract: In the experiment, a high-performance liquid chromatography and electrospray ionization-tandem mass spectrometry with selected reaction monitoring was used to simultaneously determine various classes of phytohormones, including indole-3-acetic acid, α-naphthaleneacetic acid, 2-chlorobenzoic acid, 4-chlorobenzoic acid, indole-3-butyric acid, gibberellic acid, 2,4-dichlorophenoxyacetic acid, 2-naphthoxyacetic acid, abscisic acid, 2,3,5-triiodobenzoic acid, uniconazole, paclobutrazol and 2,4-epibassinolide in rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 34 publications
(48 reference statements)
2
32
2
Order By: Relevance
“…In contrast to our results, Fan et al (2011) reported no matrix effects on the analysis of several phytohormones (including ABA) in canola. Their results are in accordance with our findings, because ABA showed a 6.6% matrix effect (Table 3), allowing its quantification by the solvent curve method (i.e., a matrix effect <10%).…”
Section: Matrix Effectscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, Fan et al (2011) reported no matrix effects on the analysis of several phytohormones (including ABA) in canola. Their results are in accordance with our findings, because ABA showed a 6.6% matrix effect (Table 3), allowing its quantification by the solvent curve method (i.e., a matrix effect <10%).…”
Section: Matrix Effectscontrasting
confidence: 99%
“…When using liquid chromatography-electrospray ionization-tandem mass spectrometry (LC-ESI-MS/MS) for plant hormone analysis, co-extracted constituents in the matrix can interfere with the analysis and cause ionization enhancement or suppression (Fan et al, 2011). The type and magnitude of the matrix effect may vary for different concentration ranges (Zrostlíková et al, 2001); thus, the use of surrogates (typically deuterated phytohormones) cannot effectively correct for interference in all cases.…”
Section: Introductionmentioning
confidence: 99%
“…LC-MS provides decisive advantages in performing identification as well as determination of analytes at trace levels. Matrix effects, however, limit the potential of LC-MS. Molecules originating from the sample matrix that coelute with the compounds of interest can interfere with the ionization process in the mass spectrometer, causing ionization suppression or enhancement, which is the so-called matrix effect (Fan et al, 2011). Ion suppression (or enhancement) might be encountered due to matrix components that co-elute with the analyte of interest.…”
Section: Hplc-ms-msmentioning
confidence: 99%
“…24 A rapid analysis of multiple hormones is possible through the relatively short dwell times typical for modern mass spectrometers. 25 In addition, the application of ultrahigh-performance liquid chromatography (UHPLC) 26 as well as solid-phase extraction (SPE)-based enrichment 27 may lead to the further improve-ment of sensitivity of phytohormone analysis.…”
Section: Introductionmentioning
confidence: 99%